A structural ambiguity analysis in sentences found in the skeleton key novel - Mahendra, I Gede; Maharani, Putu Devi; Karya, I Wayan Sidha (Institut Pariwisata dan Bisnis Internasional, 2022)
As social beings, humans need other individual to survive. In social life, humans interact and communicate with each other using languages which use to ask for help or exchange information. Often in verbal or non-verbal communication, someone provides information that has two or more different meaning thus confusing the interlocutors, this condition of information call ambiguous. This study entitle “A Structural Ambiguity Analysis In Sentences Found in The Skeleton Key Novel” is aimed to identify one of the types of surface ambiguity in the structural ambiguity in sentences found in The Skeleton Key novel, and to analyze pattern of structural ambiguity in sentences that were found in The Skeleton Key novel by tree diagrams. The data of this study were analyzed by using the qualitative method. From 12 data that were found in the data source, one of the data were analyzed as the sample of this study. From six types of surface ambiguity propose by Kriedler (1998) only one of the types was analyzed for this research. It was a coordinate head with one modifier. In this research, the researcher found that the structure of sentence structure will affect the meaning of the sentence itself. Thus the analysis of sentence structure using tree diagram will produce different meaning according to intented construction in tree diagram.